An analysis of leg muscle stretch using digital image correlation - Omkar, S. N.; Raviprakash, S.; Vishwas, S.; Kulkarni, Kiran P (Journal of Structural Engineering, 2025)
This experiment aims to examine the strain in the leg muscles when subjected to varied degrees of stretch using the technique of Digital Image Correlation (DIC). This test requires the subject to stand on a variable slope and images are captured at varying inclinations of the slope. The images are then analysed using a DIC software package which compares the images captured before and after the stretch. Through this comparison, strain plots are obtained that indicate how the strains in the calf act along the entire region of study. A comparison of the effects of varied inclinations is made. The experiment is then repeated for five other participants and the trends are observed. The effect of stretching on the two important superficial components of the leg muscles, namely the gastrocnemius muscles and the Achilles tendon, is studied. From the research, the strain distribution in the leg can be understood easily, which in turn helps in understanding the superficial muscle behaviour as well. It is also suggested that DIC can be an extremely effective non-contact analysis tool in biomechanics research.